Increasing Production Productivity by Improving Facility Layout Using the BLOCPLAN Method, Systematic Layout Planning, and Differential Evolution Algorithm - Tarigan, Ukurta; Sembiring, Meilita Tryana; Tarigan, Indah Rizkya; Syahpturi, Khalida (Jurnal Sistem Teknik Industri, 2025)
A furniture company that produces dining chairs, coffee tables, and sofa has a common problem, namely the company's inability to complete production targets within the specified time period. These general problems are the result of less efficient production paths because there is backtracking, by-passing, cross movement, and material transfer between stations that are far apart. This problem can be resolved by using improvements to the production floor layout using BLOCPLAN, Systematic Layout Planning, and Algorithms Differential Evolution. This research aims to design a production floor layout that can minimize distance, total movement moment, and material handling costs, with a line efficiency rate above 75%. The results of this research show that the proposed layout was selected using the Differential Evolution Algorithm with a displacement distance of 231.24 meters, a total displacement moment of 15,820.93 meters/month, material handling costs of IDR 1,865,920/month, and a line efficiency rate of 81.94 %.